Donantes a corazón parado. - Corral Rosillo, J.; Delgado Martín, J.A.; Fuentes Márquez, I.; Górriz, E.; Resel, Luis; Gómez Vegas, Ángel; Pérez Contín, M.J.; Rabadán, M.; Silmi Moyano, A.; Blázquez Izquierdo, J.; Álvarez Rodriguez, Joaquín; Barrio Yesa, Mª del Rosario (Clínicas Urológicas de la Complutense, 1999)
Sin resumen